Effect of Leadership Style and Work Discipline on Employee Performance at PT Toys Games Indonesia Karawaci Mall Branch (International Journal of Business and Information Technology, 2022)
This study aims to determine the effect of leadership style and work discipline on employee performance at PT Toys Games Indonesia Mall Karawaci Branch. The method used is quantitative. The sampling technique used a saturated sampling of 58 employees. The data analysis used is validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, and hypothesis testing. The results of this study are leadership style has a significant effect on employee performance with a correlation value (r) of 0.563, meaning that the relationship between leadership style variables on employee performance has a moderate level of relationship. Hypothesis testing is obtained by the value of t arithmetic > t table or (5.104 > 2.003) thus H01 is rejected and Ha1 is accepted, this shows that there is a partially significant influence between leadership style on employee performance at PT Toys Games Indonesia Mall Karwaci Branch. Work discipline has a significant effect on employee performance with a correlation value (r) of 0.596, meaning that the relationship between work discipline variables on employee performance has a moderate level of relationship. Hypothesis test obtained by t count > t table or (5.551 > 2.003) thus H02 is rejected and Ha2 is accepted, this shows that there is a partially significant influence between work discipline on employee performance at PT Toys Game Indonesia Mall Karawaci Branch. Leadership style and work discipline have a significant effect on employee performance with a correlation value (r) of 0.653, meaning that the relationship between leadership style and work discipline variables on employee performance has a strong level of relationship. Hypothesis testing obtained F arithmetic value > F table or (20,452 > 3.16) thus H03 is rejected and Ha3 is accepted, this shows that there is a simultaneous significant influence between leadership style and work discipline on employee performance at PT Toys Games Indonesia Karawaci Mall Branch.